The dermatological manifestations of extreme weather events: A comprehensive review of skin disease and vulnerability - Eva Rawlings Parker; Jessica Mo; Rachel S. Goodman (Elsevier, 2022)
As the body's most direct interface with the environment, cutaneous health is especially vulnerable to climatic factors. Anthropogenic-induced climatic change continues to accelerate, increasing the probability and severity of extreme weather events (EWE). In this review, we examine the dermatological manifestations related to EWE, such as floods, wildfires, and extreme heat. To improve awareness among dermatologists and other clinicians, the English language scientific literature was searched to identify articles linking climate change, extreme weather events, and skin manifestations. Common themes include propagation of infection and vector-borne diseases, exacerbation of underlying inflammatory conditions, and psychodermatologic implications. Secondary effects of natural disasters such as population migration, inadequate sanitation and hygiene infrastructure, and limited access to healthcare services increase the risk of climate-related skin disease. Extreme weather events also disproportionately affect certain demographic and geographic populations and exacerbate underlying disparities in marginalized populations. Improving extreme weather-related dermatological health outcomes requires a comprehensive approach in clinical practice, research endeavors, and public policy interventions with particular attention to disproportionate impacts on vulnerable populations.